Podział spółdzielni - Stecki, Leopold (Wydział Prawa i Administracji UAM, 1985)
The Polish cooperative law of 1982 introduces new institutions, among others it is a partition of the already existing cooperative. It can be performed in that manner that a new cooperative is created from the apportioned part of the existing one while the latter is acting from then on in a curtailed structure. Any cooperative can be divided unless it is in liquidation or in bankruptcy. The cooperative is divided subject to the will of at least two thirds of its members. Consequently the grounds for division are formed by the decision of the general meeting of the cooperative members taken by the majority of two thirds of votes. In course of the partition the new cooperative is being established. Its activity is regulated by the general rules of cooperative law. It is the new particular mode of forming a cooperative. Its main characteristic trait lies in the fact that the cooperative is constituted by members of other cooperative and such will can also be manifested by persons who are not becoming members of the cooperative being established in course of the division of existing one. The decision of general meeting made in case of the cooperatives partition must include: a) denomination of the cooperative being partitioned and the cooperative being formed in course of the partition, b) the list of members leaving the partitioned cooperative for the newly created one, c) approval of the balance- -sheet of the partitioned cooperative and a draft of distribution of property elements and d) a date of the cooperative's division. Provisions of the statute of cooperative formed in course of the partition cannot curtail the property rights of its members. The decision of the general meeting concerning the partition can be appealed against according to the general rules known in the cooperative law. A right to lay an action against such decision is granted to members of that cooperative and to managing board of the competent central union. Decisions of the meeting of members moving from the partitioned cooperative to the one formed in course of the partition can also be appealed against in court. A date of cooperative partition in a legal meaning is the date of entering that event in the register. If the records of partition and of establishing new cooperatives were entered by two courts at different time, then the date of registering the forming of new cooperative is decisive in the aspect the cooperatives partition. In the effect of the partition part of members of the previously existing cooperative moves to the newly created one. The property elements indicated in the „draft of distribution" are also moved for the new cooperative, they include mobilities and immobilities, technical equipement and means of production. By virtue of the law the new cooperative takes over the duties and rights of the previous one, mentioned in the „draft of distribution". It is a case of the cumamilative transfers of debts. Two cooperatives are joint and several liable for these debts. The cooperative created in course of the division takes over the employees as well. It enters into the legal relations effected by the labor contracts concluded between those employees and the cooperative which was partitioned.
Partition of a cooperative